2014
DOI: 10.1016/j.algal.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Lipid productivity and cell wall ultrastructure of six strains of Nannochloropsis: Implications for biofuel production and downstream processing

Abstract: Microalgae are generating considerable interest for third generation biodiesel production. However, appropriate strain selection is proving challenging due to the significant variation in cellular physiology, metabolic potential and genetics observed even amongst strains deemed morphologically similar. Six strains of Nannochloropsis from the CCAP culture collection were assessed for their lipid productivity and cellular structure, as proxies for oil production and harvesting ease, to assess their suitability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…The strain investigated in this study showed an analogous total lipid percentage, which was in accordance with previous results. The EPA content of the studied N. gaditana strain (7.4-28.8%) was found to be comparatively superior to that of the previously mentioned species of this genus [7,14,15].…”
Section: Resultsmentioning
confidence: 95%
“…The strain investigated in this study showed an analogous total lipid percentage, which was in accordance with previous results. The EPA content of the studied N. gaditana strain (7.4-28.8%) was found to be comparatively superior to that of the previously mentioned species of this genus [7,14,15].…”
Section: Resultsmentioning
confidence: 95%
“…Nannochloropsis is a genus of unicellular Eustigmatophyceae found in various habitats (Beacham et al, 2014). Currently, draft whole-genome sequences of N. oceanica CCMP1779 (Vieler et al, 2012) and Nannochloropsis gaditana CCMP526 (Radakovits et al, 2012) have been assembled and several genetic engineering tools established.…”
mentioning
confidence: 99%
“…Several species in the genus Nannochloropsis are recognized as oleaginous algae owing to their ability to accumulate large quantities of lipid. However, there is inter-and intra-species variation in the lipid productivity and fatty acid composition (Ma et al 2014, Beacham et al 2014. In a study of nine Nannochloropsis strains, specific growth rates were found to range from 0.07 to 0.21 day -1 while the lipid content varied from 37 to 60% of dry weight (Ma et al 2014).…”
Section: Enhancing the Lipid Profile In Nannochloropsis: Strain Choicmentioning
confidence: 99%
“…The most suitable strain depends on the desired product; strains for fish oil production should have high levels of EPA either in polar lipids for good bioavailability or as neutral TAGs for ease of extraction, whereas those for biodiesel need shorter saturated and monounsaturated fatty acids in TAGs. Significant variation is also seen in cell wall thickness among Nannochloropsis species, which could impact on both the efficiency and cost of lipid extraction, as well as the ease with which a strain can be genetically engineered (Beacham et al 2014). Furthermore the salinity of the culture medium also influences the thickness of the wall within a species, so growth conditions could be optimized to favour downstream processing (Beacham et al 2014).…”
Section: Enhancing the Lipid Profile In Nannochloropsis: Strain Choicmentioning
confidence: 99%